2015
DOI: 10.1126/scitranslmed.aaa8791
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the human visual system after retinal gene therapy in patients with Leber’s congenital amaurosis

Abstract: Much of our knowledge of the mechanisms underlying plasticity in the visual cortex in response to visual impairment, vision restoration, and environmental interactions comes from animal studies. We evaluated human brain plasticity in a group of patients with Leber’s congenital amaurosis (LCA), who regained vision through gene therapy. Using non-invasive multimodal neuroimaging methods, we demonstrated that reversing blindness with gene therapy promoted long-term structural plasticity in the visual pathways ema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 60 publications
(120 reference statements)
0
47
0
Order By: Relevance
“…18 This improvement has remained durable over at least 3 years, with observation ongoing. 18,19 In addition, a subset of participants in this study was enrolled in a separate functional magnetic resonance imaging study 20 that showed increased activation of the visual cortex and evidence of improved function and structure of the visual pathways after intervention. Other RPE65 gene therapy trials, which were administered to only one eye per individual using different gene constructs, vector formulations, or surgical approaches, have shown improvements in retinal function but variable durability of effect.…”
Section: Introductionmentioning
confidence: 99%
“…18 This improvement has remained durable over at least 3 years, with observation ongoing. 18,19 In addition, a subset of participants in this study was enrolled in a separate functional magnetic resonance imaging study 20 that showed increased activation of the visual cortex and evidence of improved function and structure of the visual pathways after intervention. Other RPE65 gene therapy trials, which were administered to only one eye per individual using different gene constructs, vector formulations, or surgical approaches, have shown improvements in retinal function but variable durability of effect.…”
Section: Introductionmentioning
confidence: 99%
“…1 These lasting cortical activations are likely related to structural improvements observed in these subjects, which, in turn, are further strengthened through visual experience. 3032 …”
Section: Discussionmentioning
confidence: 99%
“…Injections administered in this area of the retina cause preferential right visual pathway strengthening because the right temporal projections from the retina stay on the right visual cortex and do not cross to the left hemisphere. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials for a form of RP called Leber congenital amaurosis slowed photoreceptor death but did not halt degeneration (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). While there are ongoing efforts to improve this therapy, a limitation of gene-specific treatments is the vast genetic heterogeneity of RP, with more than 60 genes associated with the disorder (33)(34)(35).…”
Section: H620q/h620qmentioning
confidence: 99%